Purification of crude turpentine oil through acid degumming using phosphoric acid - Sisdikarini Dana; Sulistiawati Endah; Hakika Dhias Cahya; Sulistyo Hary (BIO Web of Conferences)
The production of bio-based materials is one of the accomplishments of the Sustainable Development Goals (SDGs), especially responsible consumption and production (SDG 12). One way to produce raw materials for the pharmaceutical industry is by utilizing waste from turpentine condensate. This study focused on turpentine waste derived from pine resin in the Trenggalek pine plantation area of East Java, Indonesia. Degumming is one of the preliminary treatments generally applied for oil refining, while acid degumming is a method of degumming. This research studied mass transfer and chemical reactions on the degumming of turpentine with phosphoric acid solutions. An amount of 100 mL of turpentine and 10 mL of 50% phosphoric acid solution was placed in a three-necked flask and stirred. The batch process was carried out at a temperature range of 40-80°C and stirred at 200 rpm for 30-120 minutes. Every 30 minutes, a 2 mL sample was taken from a three-neck flask to measure the refractive index and determine the gum concentration in the turpentine oil. Stirring the substance for two hours at 80°C resulted in the best gum removal at 44.9%.